Rain Evaporation, Snow Melt, and Entrainment at the Heart of Water Vapor Isotopic Variations in the Tropical Troposphere, According to Large‐Eddy Simulations and a Two‐Column Model. (8th April 2021) - Risi, Camille; Muller, Caroline; Blossey, Peter
Abstract: We aim at developing a simple model as an interpretative framework for the water vapor isotopic variations in the tropical troposphere over the ocean. We use large‐eddy simulations of disorganized convection in radiative‐convective equilibrium to justify the underlying assumptions of this simple model, to constrain its input parameters and to evaluate its results. We also aim at interpreting the depletion of the water vapor isotopic composition in the lower and midtroposphere as precipitation increases, which is a salient feature in tropical oceanic observations. This feature constitutes a stringent test on the relevance of our interpretative framework. Previous studies, based on observations or on models with parameterized convection, have highlighted the roles of deep convective and mesoscale downdrafts, rain evaporation, rain‐vapor diffusive exchanges, and mixing processes. The interpretative framework that we develop, valid in case of disorganized convection, is a two‐column model representing the net ascent in clouds and the net descent in the environment. We show that the mechanisms for depleting the troposphere as the precipitation rate increases all stem from the higher tropospheric relative humidity. First, when the relative humidity is larger, less snow sublimates before melting and a smaller fraction of rain evaporates. Both effects lead to more depleted rain evaporation and eventually more depleted water vapor. This mechanism dominates in regimes of large‐scale ascent. Second, the entrainment of dry air into clouds reduces the vertical isotopic gradient and limits the depletion of tropospheric water vapor. This mechanism dominates in regimes of large‐scale descent. Plain Language Summary: Water molecules can be light (one oxygen atom and two hydrogen atoms) or heavy (one hydrogen atom is replaced by a deuterium atom). These different molecules are called water isotopes, and their relative concentration in water is called the isotopic composition. The isotopic composition of the precipitation recorded in ice cores or in speleothems can be used to reconstruct past climates. However, the factors controlling the isotopic composition are complex. Here we aim at developing a simple model as an interpretative framework for the water vapor isotopic variations in the tropical troposphere over the ocean. As a guide for developing this framework, we use high‐resolution atmospheric simulations that explicitly simulate vertical motions in the storms. As a test for this framework, we try and interpret why the precipitation and water vapor in observations are more depleted when storm activity is stronger. We find that stronger storm activity, when associated with stronger large‐scale ascent, is associated with a moister troposphere. This reduces the sublimation of snow, the fraction of rain that evaporates and the dilution of cloudy air by entrainment, ultimately leading to more depleted water vapor and precipitation. Key Points: Isotopic enrichment of tropospheric water vapor by rain evaporation is stronger when drier air enhances sublimation and evaporation Entrainment of dry air weakens the vertical isotopic gradient and limits the depletion of tropospheric water vapor These mechanisms explain the increased depletion of tropospheric water vapor as tropospheric relative humidity increases